The feminine and the transgender sinthome: clinical and theoretical issues - Pierre Bonny; Romuald Hamon; Stijn Vanheule; Alexander Miller; Glenn Le Gall (Revista Latinoamericana de Psicopatologia Fundamental, 2023)
In some contemporary psychoanalytic theories, a thesis has emerged according to which gender transition can constitute a sinthome. But gender remains a much-discussed notion in Lacanian psychoanalysis, especially in France. This article contributes to the debate by questioning the notion of femininity since it seems to be an essential point in how gender studies and Lacanian sexuation theory diverge. First, we clarify the Lacanian notion of femininity and its conceptual link to the notion of sinthome. Then, we discuss the clinical case of a transgender woman for whom the question of femininity was central during her transition. Finally, we argue how gender transition might function as a sinthome and the limits to such an understanding.